Application of Augmented Reality in Teaching and Learning in Engineering Programs - Carrion Silva, Alexis Javier; Reyes Calderon, Angie Melanie; Giraldo Retuerto, Margarita; Andrade-Arenas, Laberiano (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Augmented reality is one of the new emerging technologies in the world, since its appearance was considered for many years its application in education as a tool in the student’s learning process. Taking these aspects into account, the present research article was developed, which is based on the design proposal using augmented reality in the learning process at a university in northern Lima. In which the analysis, architecture and development of a prototype was showed in detail. The result of the article was obtained by means of surveys, in the first survey it was demonstrated that the augmented reality is an unknown technology for several of the students and the feasible use in the distance education as a support in the classes, in the same way the second survey demonstrated a high interest on the part of the students at the moment of using this technology in its learning of university formation.